Dynamic Regulation of Oct1 during Mitosis by Phosphorylation and Ubiquitination - Kang, Jinsuk; Goodman, Ben; Zheng, Yixian; Tantin, Dean (PLOS ONE, 2011)
Background Transcription factor Oct1 regulates multiple cellular processes. It is known to be phosphorylated during the cell cycle and by stress, however the upstream kinases and downstream consequences are not well understood. One of these modified forms, phosphorylated at S335, lacks the ability to bind DNA. Other modification states besides phosphorylation have not been described. Methodology/Principal Findings We show that Oct1 is phosphorylated at S335 in the Oct1 DNA binding domain during M-phase by the NIMA-related kinase Nek6. Phospho-Oct1 is also ubiquitinated. Phosphorylation excludes Oct1 from mitotic chromatin. Instead, Oct1pS335 concentrates at centrosomes, mitotic spindle poles, kinetochores and the midbody. Oct1 siRNA knockdown diminishes the signal at these locations. Both Oct1 ablation and overexpression result in abnormal mitoses. S335 is important for the overexpression phenotype, implicating this residue in mitotic regulation. Oct1 depletion causes defects in spindle morphogenesis in Xenopus egg extracts, establishing a mitosis-specific function of Oct1. Oct1 colocalizes with lamin B1 at the spindle poles and midbody. At the midbody, both proteins are mutually required to correctly localize the other. We show that phospho-Oct1 is modified late in mitosis by non-canonical K11-linked polyubiquitin chains. Ubiquitination requires the anaphase-promoting complex, and we further show that the anaphase-promoting complex large subunit APC1 and Oct1pS335 interact. Conclusions/Significance These findings reveal mechanistic coupling between Oct1 phosphorylation and ubquitination during mitotic progression, and a role for Oct1 in mitosis.